MINAT BERKONTRIBUSI PADA KEPUASAN KERJA PERAWAT - Malawat, Krisna Yetti; Wigiarti, Sri Herni; Nuraeni, Tuti Sri (Universitas Islam Negeri Alauddin Makassar, 2020)
The Relationship Interest of being A Nurse with Job Satisfaction at “X”. Hospital udul bahasa Inggris. Job satisfaction has a positive impact for nurses in doing their work.The interest is a mental process that creates whether positive or negative feelings to each individual that are associated with satisfaction in work. The purpose of this research is to identify the relations interest of being a nurse and job satisfaction at